Efektivitas Model Pembelajaran Kooperatif Tipe Tea Party Tebak Kata Untuk Meningkatkan Keterampilan Memahami Isi Tembang Macapat (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
Javanese language learning includes song material which contains words that are difficult for students of Keas XI at PGRI Laboratory High School Semarang. This research aims to determine the effectiveness of the Tebak Kata type cooperative learning model in improving the ability of XI students at PGRI Laboratory Semarang High School in understanding the content of the macapat song. This research is a true experimental type of research. The population used in this research was all 92 students at SMA PGRI Semarang Laboratory. The sample taken in this research was a purposive sampling technique which resulted in 22 classes XI IPS 1 being the control class and 24 XI IPA 2 being the experimental class. The research instrument uses tests in the form of pretest-posttest questions and non-tests in the form of observations and interviews. The results of this research, seen from the results of hypothesis testing using the paired sample t-test, show that there is an increase in the experimental and control classes. In the effectiveness test using the N-gain percent test, the experimental class was included in the "Medium" category, while the control class was included in the "Less Effective" category. It can be concluded that the Tea Party Guess the Word type cooperative learning model is effective for improving skills in understanding the content of Macapat songs compared to using conventional learning models. This learning model tends to be one-way, so students are less active in the learning process